Culturally Relevant Programming in Action: A Case Study of a Marriage Education Program for African American Couples - Patricia L. Erwin (Adult Education Research Conference, 2014)
The purpose of this study was to understand how a preventive intervention, specifically a marriage education program, was designed to meet the needs of African American couples.